Tripartite interactions between filamentous Pf4 bacteriophage, Pseudomonas aeruginosa, and bacterivorous nematodes. - Caleb M Schwartzkopf; Autumn J Robinson; Mary Ellenbecker; Dominick R Faith; Amelia K Schmidt; Diane M Brooks; Lincoln Lewerke; Ekaterina Voronina; Ajai A Dandekar; Patrick R Secor (PLoS Pathogens, 2023)
The opportunistic pathogen Pseudomonas aeruginosa PAO1 is infected by the filamentous bacteriophage Pf4. Pf4 virions promote biofilm formation, protect bacteria from antibiotics, and modulate animal immune responses in ways that promote infection. Furthermore, strains cured of their Pf4 infection (ΔPf4) are less virulent in animal models of infection. Consistently, we find that strain ΔPf4 is less virulent in a Caenorhabditis elegans nematode infection model. However, our data indicate that PQS quorum sensing is activated and production of the pigment pyocyanin, a potent virulence factor, is enhanced in strain ΔPf4. The reduced virulence of ΔPf4 despite high levels of pyocyanin production may be explained by our finding that C. elegans mutants unable to sense bacterial pigments through the aryl hydrocarbon receptor are more susceptible to ΔPf4 infection compared to wild-type C. elegans. Collectively, our data support a model where suppression of quorum-regulated virulence factors by Pf4 allows P. aeruginosa to evade detection by innate host immune responses.